Identification of Five Quality Needs for Rheumatology (Text Analysis and Literature Review) - Pallua, Johannes; Schirmer, Michael (Frontiers in Medicine, 2021)
Background: While the use of the term "quality" in industry relates to the basic idea of making processes measurable and standardizing processes, medicine focuses on achieving health goals that go far beyond the mere implementation of diagnostic and therapeutic processes. However, the quality management systems used are often simple, self-created concepts that concentrate on administrative processes without considering the quality of the results, which is essential for the patient. For several rheumatic diseases, both outcome and treatment goals have been defined. This work summarises current mainstreams of strategies with published quality efforts in rheumatology. Methods: PubMed, Cochrane Library, and Web of Science were used to search for studies, and additional manual searches were carried out. Screening and content evaluation were carried out using the PRISMA-P 2015 checklist. After duplicate search in the Endnote reference management software (version X9.1), the software Rayyan QCRI (https://rayyan.qcri.org) was applied to check for predefined inclusion and exclusion criteria. Abstracts and full texts were screened and rated using Voyant Tools (www.voyant.tools.org). Key issues were identified using the collocate analysis. Results: The number of selected publications was small but specific (14 relevant correlations with coefficients > 0.8). Using trend analysis, 15 publications with relative frequency of keywords > 0.0125 were used for content analysis, revealing 5 quality needs:. The treat to target (T2T) initiative was identified as fundamental paradigm. Outcome parameters required for T2T also allow quality assessments in routine clinical work. Quality care by multidisciplinary teams also focusing on polypharmacy and other quality aspects become essential, A global software platform to assess quality aspects is missing. Such an approach requires reporting of multiple outcome parameters according to evidence-based clinical guidelines and recommendations for the different rheumatic diseases. All health aspects defined by the WHO (physical, mental and social health) have to be integrated into the management of rheumatic patients. Conclusion: For the future, quality projects need goals defined by T2T based initiatives in routine clinical work, secondary quality goals include multidisciplinary cooperation and reduction of polypharmacy. Quality indicators and standards in different health systems will provide new information to optimize patients’ care in different health systems.